Paraguay : Selected Issues. (IMF Staff Country Reports; Country Report, 2010)
This technical paper focuses on the challenges faced by Paraguay's budget resources. Paraguay's government should adopt a forward-looking fiscal strategy. The strategy's main goals should be to contain budget dependence on Itaipu revenues, preserve fiscal discipline, and allow for the gradual and sustainable transformation of the envisaged, yet temporary, windfall into other forms of financial, physical, and human capital. The creation of a special fund could help mobilize public support for saving part of the windfall and building a buffer for the future.